Cardinal Virtues in Sport: Prudentia - Jernej Pisk (Sciendo, 2015)
Cardinal virtues present one of the oldest anthropological theories and ethical systems in the western philosophical tradition. Among other great ancient philosophers, Plato talked about four main virtues: prudence (practical wisdom), justice, fortitude (courage), and temperance (moderation). As these virtues are not arbitrary, but instead correspond to some fundamental characteristics of human beings, they are not only useful for moral decision-making, but they also present an original anthropological theory. This paper focuses on the role of prudence in sports.